Effect of Pruning Intensities and Pasture Combinations on Prod ctivity of Ber- Based HÂ«?rtipastoralSystem - Kumar, Sunil; Ram, S N (Annals of Arid Zone, 2016)
Ber-based hortipastoral system was studied for four consecutive ye rs (2001-02 to 2004-05) involving ber tree with different pruning intensities to utilize understo ey through different pasture combinations for increasing productivity and profitability. Ov r the four years m dium pruned trees (40 cm of secondary branches) produced maximum fruit (26.28 kg fruit tree-I) followed by light (23.41 kg tree-I) and severely pruned trees (18.31 kg tree-I). Severely pruned trees produced significantly higher pasture (4.05 t DM ha-I) followed by medium (4.02 t DM ha-I) and light pruned trees (3.77 t D Mha-I). Among pastureco[1 binations, Guinea grass + Stylosanthes hamata produced significantly higher forage (6.33 DM ha-I) .is compared to Dinanath + Guinea grass + S. hamata (5.06 t DM ha-I), Dinanath + S. f(3.28 t DM ha-I) and natural pasture (1.32 t DM ha-I). Related econo ics of ber ’(lb-year-old plantation)-based hortipastoral system indicated that maximum bene ’t:cost ratio (1:3.99) over four years of experiment was obtained when lO-year-old ber trees w re medium pruned along with understorey pasture of Guinea grass + S. hamata.